(untitled) (Journal of Geography and Environmental Management, 2018)
The article discusses the influence of presowing flooding of irrigated rice array on the seasonal dynamics of soil processes. As well as the characteristic of negative processes and their consequences that arise after the flooding of rice soils of the array, for example: lack of oxygen, harmful effects of hydrogen sulfide in the rice culture. The paper describes the current ecological state takyr soils Akdalaarray degradation and waterlogging of soils. These processes are consequences of depressed economic conditions and the use of pesticides and fertilizers in agriculture. In the last desyatiletiya in connection with the deterioration of reclamation condition of irrigated soils in the arrays significantly decreased the fertility continues dehumification and ecological condition of soils. In some regions of Kazakhstan, much of the land unusable due to salinity. Of the above environmental issues affect the reduction of humus, nutrients, physico-chemical and biological properties of soil, which in turn affects productivity and quality of rice. This article describes the environmental problems of Kazakhstan soils associated with zatuplenie array. The study of the influence of presowing flooding of irrigated rice array on the seasonal dynamics of soil processes is very important for our country. The analysis of literary sources shows that in the rice areas of the Republic has developed an environmentally unfavorable situation. This reduces the potential for socio-economic development of the Republic, particularly, the resource base of the rural economy. In this regard, of particular urgency is the creation of a scientific and theoretical foundations of the holistic concept of fertility reproduction of periodically flooded soils.